Efforts to improve the work skills of Tunas Harapan Batang Serangan Vocational School students - Nasib; Roni Juliansyah; Amin Hou; Tambunan, Debora; Rivai, Ahmad; Chaniago, Sabaruddin; Martin; Rifda Daulay, Zulia; Winda Sari, Vina; Harianto, Adi (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Students must get training that imparts essential skills to effectively confront obstacles in the workforce and remain competitive. An essential training for vocational high school students is the development of a curriculum vitae (CV) and preparation for job interviews. This program is highly advantageous for SMK Tunas Harapan students and is a community service initiative designed to enhance their preparedness for the professional realm. The execution of this program arises from the imperative for vocational high school graduates to acquire the competencies necessary for crafting an appealing CV and effectively preparing for job interviews, since they represent the preliminary stages toward workforce entry. This training comprises two primary sessions. The initial session addresses proficient CV composition strategies and best methods for emphasizing talents and experience. The second session addresses employment interview preparation, encompassing effective communication strategies, professional demeanor, and responses to frequently asked interview questions. This workshop includes an interview simulation to provide students with practical experience. This training has effectively enhanced students' confidence in crafting CVs and preparing for job interviews. We anticipate that SMK Tunas Harapan students will be more competitive and prepared to confront challenges in the workforce with the skills they have learned.